M = ∫ 0 π / 2 sin x − 1 ln ( sin x ) d x . Find ⌊ 1 0 M ⌋ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Cool problem ! @Harsh Shrivastava ! Keep posting such problems !
Note1:
∫ sin ( x ) − 1 1 ⋅ sin ( x ) + 1 sin ( x ) + 1 d x = ∫ − cos 2 ( x ) sin ( x ) + − cos 2 ( x ) 1 = − ( ∫ sec ( x ) tan ( x ) + ∫ s e c 2 ( x ) ) = − ( sec ( x ) + tan ( x ) ) + C
Note2:
∫ csc ( x ) ⋅ csc ( x ) + cot ( x ) csc ( x ) + cot ( x ) d x = − ∫ csc ( x ) + cot ( x ) − csc 2 ( x ) − csc ( x ) cot ( x ) d x = − ln ( csc ( x ) + cot ( x ) ) + C
Solution:
u = ln ( sin ( x ) ) d u = cot ( x ) d v = sin ( x ) − 1 d x v = − ( sec ( x ) + tan ( x ) )
∫ sin ( x ) − 1 ln ( sin ( x ) ) d x ∫ 0 π / 2 sin ( x ) − 1 ln ( sin ( x ) ) d x x → π / 2 x → 0 ∫ 0 π / 2 sin ( x ) − 1 ln ( sin ( x ) ) d x = − ln ( sin ( x ) ) ⋅ ( sec ( x ) + tan ( x ) ) + ∫ cot ( x ) ⋅ ( sec ( x ) + tan ( x ) ) d x = − ln ( sin ( x ) ) ⋅ ( sec ( x ) + tan ( x ) ) + ∫ ( csc ( x ) + 1 ) d x = − ln ( sin ( x ) ) ⋅ ( sec ( x ) + tan ( x ) ) − ln ( csc ( x ) + cot ( x ) ) + x = − ln ( sin ( x ) ) ⋅ ( sec ( x ) + tan ( x ) ) − ln ( 1 + cos ( x ) ) + ln ( s i n ( x ) ) + x = − ln ( sin ( x ) ) ⋅ ( sec ( x ) + tan ( x ) − 1 ) − ln ( 1 + cos ( x ) ) + x = − ln ( sin ( x ) ) ⋅ ( sec ( x ) + tan ( x ) − 1 ) − ln ( 1 + cos ( x ) ) + x ∣ 0 π / 2 − ln ( sin ( x ) ) ⋅ ( sec ( x ) + tan ( x ) − 1 ) → 0 − ln ( sin ( x ) ) ⋅ ( sec ( x ) + tan ( x ) − 1 ) → 0 = 2 π + ln ( 2 ) ≈ 2 . 2 6
Problem Loading...
Note Loading...
Set Loading...
A couple of changes of variable gives M = ∫ 0 2 1 π sin x − 1 ln ( sin x ) d x = = ∫ 0 2 1 π cos y − 1 ln ( cos y ) d y = − 2 1 ∫ 0 2 1 π ln ( cos y ) c o s e c 2 2 1 y d y − ∫ 1 ∞ ln ( u 2 + 1 u 2 − 1 ) d u = ∫ 1 ∞ ln ( u 2 − 1 u 2 + 1 ) d u using first y = 2 1 π − x and then u = cot 2 1 y . Since this integral is improper, being both infinite and with a singularity at u = 1 , we shall first integrate from a > 1 to X , and take limits. Integrating by parts gives ∫ a X ln ( u 2 − 1 u 2 + 1 ) d u = = = [ u ln ( u 2 − 1 u 2 + 1 ) ] a X + 4 ∫ a X u 4 − 1 u 2 d u [ u ln ( u 2 − 1 u 2 + 1 ) ] a X + ∫ a X ( u 2 + 1 2 + u − 1 1 − u + 1 1 ) d u [ u ln ( u 2 − 1 u 2 + 1 ) + 2 tan − 1 u + ln ( u + 1 u − 1 ) ] a X Now X ln ( X 2 − 1 X 2 + 1 ) + 2 tan − 1 X + ln ( X + 1 X − 1 ) = X ln ( 1 − X − 2 1 + X − 2 ) + 2 tan − 1 X + ln ( 1 + X − 1 1 − X − 1 ) which tends to 0 + π + 0 = π as X → ∞ , and hence ∫ a ∞ ln ( u 2 − 1 u 2 + 1 ) d u = = π − a ln ( a 2 − 1 a 2 + 1 ) − 2 tan − 1 a − ln ( a + 1 a − 1 ) π − 2 tan − 1 a − a ln ( a 2 + 1 ) + ( a + 1 ) ln ( a + 1 ) + ( a − 1 ) ln ( a − 1 ) for any a > 1 ; this tends to M = π − 2 tan − 1 1 − ln 2 + 2 ln 2 + 0 = 2 1 π + ln 2 as a → 1 . The answer is ⌊ 1 0 M ⌋ = ⌊ 5 π + 1 0 ln 2 ⌋ = 2 2 .